COVID-19 in children and the influence on the employment activity of their female caregivers: A cross sectional gender perspective study - Jaime Trujillo, Catalina; Herrera Olano, Natalia; Rico Gutiérrez, Kevin; Medellín, Daniela; Sánchez, Paola; Mesa-Rubio, María Lucía; Naranjo, Melisa Sofía; Moreno, Sergio Mauricio; Bonilla, Carolina; Barrera, Pedro; Restrepo-Gualteros, Sonia M.; Mejia, Luz Marina; et al. (Frontiers in Global Women's Health, 2023)
Introduction During the COVID-19 pandemic, women disproportionately assume more unpaid activities, affecting their employment. Objective Describe the influence of COVID-19 on the employment of caregivers of children and adolescents from a gender perspective. Methods Cross-sectional study in three high-complexity hospitals in Bogotá, Colombia from April 2020 to June 2021. A subsample of the FARA cohort was taken, including those patients with a positive test for SARS-COV2. We took as our analysis category children older than 8 years and younger than 18 years who had a positive SARS-COV2 test, as well as, caregivers of all children with a positive SARS-COV2 test. This subsample was drawn from the FARA cohort. A survey was applied to them. We carried out a descriptive and stratified analysis by age group, educational, and socioeconomic level. Results We included 60 surveys of caregivers and 10 surveys of children. The main caregiver in 94.8% of the cases was a female. At the beginning of the pandemic, 63.3% of the caregivers were employed, and 78.9% of those lost their employment. The vast majority of these caregiver were women (96.6%, n = 29). A predominance of loss of work activity was documented in caregivers of children in early childhood 66.6% (n = 20), with lower education 66.6% (n = 20), and from lower strata 56.6% (n = 17). Conclusion Caregivers of children with COVID-19 with low educational levels and lower socioeconomic conditions, as well as those with children under 5 years showed greater likelihood of employment loss between the interviewed subsample.